Issues and Challenges of Ghana School Feeding Programme in the KEEA Municipality Ghana - Akuamoah-Boateng, Clara; Sam- Tagoe, Josephine (Advances in Social Sciences Research Journal, 2018)
Ghana as a developing country embraces formal education is pivotal in its development agenda. Furtherance to this agenda, Ghana was among the first ten developing countries in Sub-Saharan Africa to implement a School Feeding Programme using the NEPAD model. The long term goal of the School Feeding Programme in Ghana, is to contribute to the achievement of the Millennium Development goals (MDGs) 1&2 which aim at eradicating extreme poverty and hunger and to achieve universal primary education. Specifically, the school feeding programme in Ghana seeks to motivate parents to send their wards to school, improve school attendance, participation and retention and to improve the nutritional status of primary children in vulnerable communities in the country. Empirical research studies available suggest that the programme has witness some successes since its inception 2005, in areas such as primary school enrollment, participation and retention. However, it appears the programme is bedeviled with some of implementation challenges that pose serious threat to achieving the lofty benefits enshrined in the long term goals and sustainability of the programme. This paper sought to examine the issues and challenges of the GSFP in the KEEA Municipality of the Central Region of Ghana and offer some suggestions and recommendations for the improvement and sustainability of the programme.